2014
DOI: 10.2478/s11536-013-0334-7
|View full text |Cite
|
Sign up to set email alerts
|

Sutures in abdominal surgery: biomechanical study and clinical application

Abstract: AbstractThe aim of this study is to improve treatment results and SSI prevention by differential usage of the contemporary suture materials and choice of proper suturing technique. To simulate suturing process and compared two suturing techniques, two FE models were developed. Finite-element analysis (FEA) was based on experimental data of contemporary commercial sutures and soft tissue properties. We applied obtained results for abdominal wall closure in rats and compared non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A wide variability in the mechanical properties of wounds can be found in the literature. For example, Ibrahim et al 15 reported E values of a few kPa for uninjured human skin, whereas Samartsev et al 16 obtained elastic moduli of a few GPa in their experiments with sutured samples. In the current study, we performed simulations within a wide range of E values for the SWs, namely 0.1 MPa ≤ E w ≤ 10,000 MPa.…”
Section: Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variability in the mechanical properties of wounds can be found in the literature. For example, Ibrahim et al 15 reported E values of a few kPa for uninjured human skin, whereas Samartsev et al 16 obtained elastic moduli of a few GPa in their experiments with sutured samples. In the current study, we performed simulations within a wide range of E values for the SWs, namely 0.1 MPa ≤ E w ≤ 10,000 MPa.…”
Section: Models and Methodsmentioning
confidence: 99%
“…In the current study, we performed simulations within a wide range of E values for the SWs, namely 0.1 MPa ≤ E w ≤ 10,000 MPa. The Poisson ratio for SW tissue was set to ν w = 0.40 16 .…”
Section: Models and Methodsmentioning
confidence: 99%
“…The posterior rectus sheath is reapproximated in the midline with a running absorbable suture. [23]. The mesh is placed in the retromuscular space and secured with transabdominal permanent sutures and is covered by reapproximation of the anterior sheath in the midline.…”
Section: Posterior Components Separationmentioning
confidence: 99%